Time Delay MIMO Decoupling Control Based on DOB-SVM Inverse System - Xie Peizhang; Zhou Xingpeng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The formation of potentially harmful trihalomethanes (THM) when using chlorine as a sanitizer in water supplies has led to a need for better control algorithm. Sanitizer dosing is a system with large time delay, non-linear, time-varying and multi models, also couple is introduced to the system because of multi tunnels multi pools structure (MTMP). Improved time-delay DOB based on SVM inverse system is proposed in this paper. Support Vector Machine (SVM) is used to identify the inverse system due to that the mathematical model will not be known precisely, then this inverse system cascades the original system so that time-delay pseudo-linearization system can be obtained. Meanwhile improved time-delay DOB is designed to overcome model mismatch, disturbance and time delay. Application results in waterworks at Suzhou (China) show that the method is able to resist the disturbance and improve the robustness; also the lower unit consumption (more than 9%) of sanitizer is obtained. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3670